The impact of barium oxide on physical, structural, optical, and shielding features of sodium zinc borate glass - Mhareb, M.H.A.; Alqahtani, Muna; Alshahri, Fatimh; Alajerami, Y.S.M.; Saleh, Noha; Alonizan, N.; Sayyed, M.I.; Ashiq, M.G.B.; Ghrib, Taher; Al-Dhafar, Sarah Ibrahim; Alayed, Tasneem; Morsy, Mohamed A. (Journal of non-crystalline solids, 2020)
The study illustrates the impact of barium oxide (BaO) on structural, physical, optical, and radiation shielding features of a series of multi-component of barium-containing borate-based glasses, namely Sodium Zinc Borate Glass. The amorphous nature of each glass material was confirmed by X-ray diffraction (XRD) analysis. Fourier-Transform-Infrared (FTIR) was used to identify the BO3-BO4 distribution and how the variation of Ba-concentrations affects this distribution. The results show that the increase of barium content increases the density of glasses and, in turn, reduces their bandgap. The investigation of the shielding properties at different energies (0.01–10 MeV) by Phy-X program indicates that the high-density of Ba-30 exhibited the best performance in terms of attenuation factor. On the other hand, the samples Ba-0 and Ba-15 show the highest durability results (lowest dissolving rate). These outcomes indicate that the glass samples exhibited promising radiation shielding properties for different applications.